PENGARUH PERBEDAAN WAKTU PENAHANAN SUHU STABIL (HOLDING TIME) TERHADAP KEKERASAN LOGAM - Margono Margono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
Hardening was attaching to steel to get high resistance, strengthens, and better fatigue limit. This hardening was done in few steps such, pre-treatment, treatment, holding time and cooling. The reach hardness depends on material carbon content, treatment temperature, holding time and rapid cooling. The hardness of Amuntit steel depends on the holding time factor. Holding time is the time which is material needs to get homogeneities in the same temperature. The experiment shows that the hardness increase in the first ten minutes holding time, from 34,24 HRC to 60,08 HRC. And 62,693 HRC at 20 minutes later, 64,52 HRC at 30 minutes later, and reach the maximum hardness 65,146 HRC at the last 40 minutes holding. The conclusion of this experiment is holding time influences the hardness beside the treatment of temperature and cooling rapid. So, we can decide the hardness we take by the holding time factor.